CHARACTERISTICS OF FUNDAMENTAL CULTURAL SCIENCE - G. Nishonboyeva (Scholar Express Journal, 2024)
This article discusses the importance of modern cultural studies, its current topics, main goals and tasks
Keywords: culture; cultural history and theory; cultural activity; cultural space